Multifunctional fiber reinforced polymer composites using carbon and boron nitride nanotubes. (December 2017) - Ashrafi, Behnam; Jakubinek, Michael B.; Martinez-Rubi, Yadienka; Rahmat, Meysam; Djokic, Drazen; Laqua, Kurtis; Park, Daesun; Kim, Keun-Su; Simard, Benoit; Yousefpour, Ali
Abstract: Recent progress in nanotechnology has made several nano-based materials available with the potential to address limitations of conventional fiber reinforced polymer composites, particularly in reference to multifunctional structures. Carbon nanotubes (CNTs) are the most prevalent case and offer amazing properties at the individual nanotube level. There are already a few high-profile examples of the use of CNTs in space structures to provide added electrical conductivity for static dissipation and electromagnetic shielding. Boron nitride nanotubes (BNNTs), which are structurally analogous to CNTs, also present a range of attractive properties. Like the more widely explored CNTs, individual BNNTs display remarkable mechanical properties and high thermal conductivity but with contrasting functional attributes including substantially higher thermal stability, high electrical insulation, polarizability, high neutron absorption and transparency to visible light. This presents the potential of employing either or both BNNTs and CNTs to achieve a range of lightweight, functional composites for space structures. Here we present the case for application of BNNTs, in addition to CNTs, in space structures and describe recent advances in BNNT production at the National Research Council Canada (NRC) that have, for the first time, provided sufficiently large quantities to enable commercialization of high-quality BNNTs and accelerate development of chemistry, composites and applications based on BNNTs. Early demonstrations showing the fabrication and limited structural testing of polymer matrix composites, including glass fiber-reinforced composite panels containing BNNTs will be discussed. Abstract : Recent BNNT production advances are making BNNTs more broadly available. BNNT buckypaper composite resulted in superior Young's modulus as compared to the similar CNTs. Hybrid glass fiber composites based on BNNTs were successfully prepared using VARTM and wet layup. The infiltration of BNNT-modified resin into glass fiber fabric during VARTM resulted in BNNT filtration. Laminates containing 1 wt% BNNTs resulted in 25% improvement of the specific fracture energy per area.